Number of finishers and performance of age group women and men in longdistance running: comparison among 10km, half-marathon and marathon races in Oslo (2020)
The aim of the present study was to examine the number of ﬁnishers and performance trends in 10 km, half-marathon and marathon races in Oslo. Data (total 115,725 ﬁnishers; women, n = 50,595; men, n = 65,130) from 10 km, half-marathon and marathon races in Oslo from 2008 to 2018 were analysed considering number, sex, age and running speed of ﬁnishers. The total men-towomen ratio was the smallest in the 10 km race (0.60) and the largest in the marathon (3.86) (p < 0.01, φ = 0.28). In both women and men, the slowest running speed was shown in the older age groups (p < 0.01). Based on the ﬁndings of the present study, it was concluded that relatively more women ﬁnished a 10 km and less a half-marathon and a marathon. Our results indicated that the sex diﬀerence in performance was attenuated in the longer race distances and older age groups.